Forensic ecogenomics : the application of microbial ecology analyses in forensic contexts - Ralebitso-Senior, T. Komang (Academic Press, 2018)
Forensic Ecogenomics: The Application of Microbial Ecology Analyses in Forensic Contexts provides intelligence on important topics, including environmental sample provenance, how to indicate the body decomposition timeline to support postmortem interval (PMI) and postmortem submersion interval (PMSI) estimates, and how to enhance identification of clandestine and transit grave locations. A diverse group of international experts have come together to present a clear perspective of forensic ecogenomics that encapsulates cutting-edge, topical and relevant cross-disciplinary approaches vital to the field. Considers the effects of decomposition on bacterial, fungal and mesofaunal populations in pristine ecosystemsExamines the role of the microbiome, necrobiome and thanatomicrobiome in postmortem interval estimationsFocuses on the application of different analytical techniques across forensics to enhance/expand the crime scene investigation toolkitWritten by a wide range of international experts in their respective fields.